(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Managing deteriorating inventory in mechatronics presents numerous opportunities. In today’s world, nearly every industry utilizes mechatronic tools and processes to slow deterioration, thereby reducing carbon emissions. Given the complexity of global warming, many countries are investing in various initiatives and promoting eco-friendly business practices to minimize carbon emissions. This study examines a two-warehouse inventory model for deteriorating goods that emit carbon. Our focus is on minimizing carbon-emitting items during transportation. Reducing emissions from deteriorating inventory requires a comprehensive strategy that involves multiple supply chain partners and prioritizes environmental sustainability. By adopting green technologies, companies can effectively lower carbon dioxide emissions. In this model, demand is influenced by selling price, and partial backlogging is also considered. Additionally, incorporating time-dependent holding costs enhances the model’s applicability. The primary goal of this study is to optimize overall cycle time and costs associated with green technology investments. By optimizing these factors, businesses can manage deteriorating inventory more efficiently while mitigating environmental impacts. Integrating all these elements, we propose an optimized inventory model for deteriorating goods, factoring in selling price and carbon emissions under green technology investment. The assumptions in this study suggest that the cost function is highly nonlinear, leading to a constrained optimization problem. The model is solved using an algorithm implemented in Mathematica software. A numerical example is provided to illustrate the model’s application, followed by a sensitivity analysis. Finally, the optimal solution is visually represented through a graphical illustration.